RPL routing protocol performance under sinkhole and selective forwarding attack: experimental and simulated evaluation - Bimal H. Patel; Parth Shah (Universitas Ahmad Dahlan, 2020)
To make possible dream of connecting 30 billion smart devices assessable from anywhere, anytime and to fuel the engine growth of Internet of things (IoT) both in terms of physical and virtual things, Internet Engineering Task Force (IETF) came up with a concept of 6LoWPAN possessing characteristics like low power, bandwidth and cost. To bridge the routing gap and to collaborate between low power private area network and the outside world, IETF ROLL group proposed IPv6 based lightweight standard RPL (Routing protocol for low power and lossy networks). Due to large chunks of random data generated on daily basis security either externally or internally always remain bigger threat which may lead to devastation and eventually degrades the quality of service parameters affecting network resources. This paper evaluates and compare the effect of internal attacks like sinkhole and selective forwarding attacks on routing protocol for low power and lossy network topology. Widely known IoT operating system Contiki and Cooja as the simulator are used to analyse different consequences on low power and lossy network.